2017
DOI: 10.2147/ott.s133756
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nimotuzumab combined with chemoradiotherapy in Chinese patients with locally advanced cervical cancer

Abstract: ObjectiveTo evaluate efficacy and safety of nimotuzumab combined with chemotherapy and radiotherapy in women with locally advanced cervical cancer.Materials and methodsWomen with locally advanced cervical cancer (stage IIB, III, or IVA) who experienced relapse after first-line chemoradiotherapy and one or more lines of palliative chemotherapy were enrolled. All patients received nimotuzumab weekly at 200 mg/m2 as single agent for 4 weeks (induction phase), then concurrent with 6 cycles (21-day per cycle) of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Nimotuzumab, as China's rst humanized anti-EGFR monoclonal antibody, can signi cantly improve the 3-year OS for nasopharyngeal carcinoma in combination with CCRT (9). Furthermore, the same trend of increasing e cacy can also be seen in some other clinical studies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 68%
“…Nimotuzumab, as China's rst humanized anti-EGFR monoclonal antibody, can signi cantly improve the 3-year OS for nasopharyngeal carcinoma in combination with CCRT (9). Furthermore, the same trend of increasing e cacy can also be seen in some other clinical studies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 68%
“…The results showed that 11 patients had partial relief of symptoms; 59 patients were stable; the rate of disease control reached 88%. Drug side effects and safety were also within acceptable limits ( 33 ). In another study, 28 patients with locally advanced cervical cancer received preoperative neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Because of its ability to bind EGFR, nimotuzumab can competitively interfere with the binding of EGF to EGFR, resulting in the blockade of downstream signaling pathways, inhibiting tumor cell proliferation, promoting tumor cell apoptosis, and enhancing the efficacy of radio- and/or chemotherapy. Although nimotuzumab has been used less frequently in treating cervical cancer, several studies have shown that the combination of nimotuzumab with radio-chemotherapy for locally advanced cervical cancer has a very reliable treatment effect ( 31 – 33 ). Nimotuzumab is therefore a promising option for preoperative neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As China's first humanized anti-EGFR monoclonal antibody, nimotuzumab has been shown to significantly improve the 3-year OS for nasopharyngeal carcinoma in combination with CCRT (9). Furthermore, the same trend of increasing efficacy can also be seen in other clinical studies of LACC (9)(10)(11), but these studies have some limitations such as single arm study or small sample size, which needs more clinical studies to prove this conclusion. In our study, we obtained the efficacy and safety data of 120 patients with LACC who received CCRT with or without nimotuzumab, observed and compared the efficacy and safety of the two groups of patients.…”
Section: Introductionmentioning
confidence: 93%